Low cost composites for vacuum insulation core material. (September 2016) - Chang, Boyce; Zhong, Landi; Akinc, Mufit
Abstract: Vacuum insulation technology provides unprecedented performance and its applications have expanded, particularly in the form of vacuum insulation panels (VIP). One of the challenges of using VIP include greater cost compared to traditional insulation because fumed silica is commonly used as the core material. The demand for low cost material with comparable service life to fumed silica constantly grows. Diatomaceous earth (DE) and glass bubbles (GB) represent alternative materials that have potential for cost effective VIP applications. The pore size distribution of the DE was determined quantitatively by mercury porosimetry and nitrogen sorption. The majority of pores in DE are ranged around 1 μm. The average pore size of GB was estimated to be 50 μm via scanning electron microscopy. Subsequently, the relationship between pore size and gaseous thermal conductivity was established using the Kaganer relation. Thermal conductivity measurements were made using the transient plane source technique, which produces higher values compared to steady state methods such as guarded hot plate. Therein, fumed silica was used as a baseline for all measurements performed in this study. DE composites showed very promising results, with its thermal conductivity only 26% higher than pure fumed silica below 10 4  Pa. Highlights: Potential use of Diatomaceous Earth in vacuum insulation panels is demonstrated. The relationship between thermal conductivity and porosity of Diatomaceous Earth composites was modeled by Landauer relation. The thermal conductivity of Diatomaceous Earth containing composites is determined largely by the porosity and pore size. Diatomaceous earth/fumed silica composites appear to be a viable core material.